PERLUASAN MODEL PENERIMAAN TEKNOLOGI PADA ROBOT BARISTA DI FAMILYMART JAKARTA - Kevin Gustian Yulius; Myrza Rahmanita (Jurnal Ilmiah Global Education, 2023)
The integration of technology in every industry is inevitable, including the food and beverage service. The use of robot barista in Jakarta is a first and worthy of investigating the acceptance intentions of the people who use them. This research aims to analyze the factors that influence consumer attitudes and acceptance intentions towards robot baristas. The model used is E-TAM, an extension of the technology acceptance model. A quantitative explanatory approach with PLS-SEM is employed in this study, using a purposive sampling technique. The research instrument used is an online questionnaire with 160 samples. Data processing using SMART PLS shows relevant results consistent with previous research. Only the perception of innovation does not influence acceptance intentions due to cultural background differences among the population. Future research should attempt to use samples with other demographic characteristics and include other exogenous variables.